Report on temporary employment agencies and temporary agency work: a comparative analysis of the law on temporary work agencies and the social and economic implications of temporary work in 13 European countries - Countouris, Nicola; Deakin, Simon; Freedland, Mark; Koukiadaki, Aristea; Prassl, Jeremias (Geneva, 2016)
"This report was produced by a group of independent experts, all of them labour lawyers and most of them academic labour lawyers, with a view of assisting the International Labour Office in the context of the ongoing technical assistance programme developed with the Greek Government in a number of areas, including “labour legislation to regulate collective dismissals”. As is widely known, since May 2010, the Union’s Euro-area Member States and the International Monetary Fund (IMF) have been providing financial support to Greece through an Economic Adjustment Programme in the context of a sharp deterioration in the country’s financing conditions. This support has been accompanied by a request on the part of the lending institutions’ representatives to implement a number of reforms aimed at improving the competitiveness of the Greek economy. Amongst a series of detailed specifications, Greece has been asked to adopt “reforms [that] will ease interpretation of and foster compliance with labour laws with a view to bring legislation in line with EU best prac-tices, and to this end a review will be carried out […], comparing Greek regulations on temporary employment, scope of temporary employment agencies […] with those in other EU Member States”."